Modelling Facebook usage among university students in Thailand: the role of emotional attachment in an extended technology acceptance model. Issue 4 (18th May 2016) - Teo, Timothy
Abstract : The aim of this study is to examine the factors that influenced the use of Facebook among university students. Using an extended technology acceptance model (TAM) with emotional attachment (EA) as an external variable, a sample of 498 students from a public-funded Thailand university were surveyed on their responses to five variables hypothesized to predict their actual use of Facebook. Data were analysed using structural equation modelling and the results showed that perceived usefulness (PU), attitude towards technology use (ATU), and EA had direct and significant influences on actual use, while perceived ease of use (PEU) was an indirect determinant of Facebook use. EA has direct and significant influences on all core variables in the TAM: PU; PEU; ATU; and actual use. Together, the PU, ATU, and EA explained 35.1% of the variance in students' usage of Facebook. Relatively, the variation in ATU and PU accounted by their determinants amounted to 55.5% and 50.2%, respectively.